Analisis Efisiensi Proses Penentuan Harga Perkiraan Sendiri menggunakan Teori Antrian pada PTPN I Regional 7 - Azzahra, Iqlima Dita; Arfi, Eristia (Transcendent Journal of Mathematics and Applications, 2024)
This study aims to analyze the efficiency of the process for determining the Estimated Own Cost (HPS) by considering the number of incoming HPS packages and the average time taken to calculate HPS. The method used in this research is queueing theory with a FIFO (First In, First Out) queue discipline and a Multi-Channel Single-Phase (M/M/S) queueing model, utilizing historical data of incoming HPS packages from February to July 2024. The results of the analysis show that the queueing system at the HPS Subdivision of PTPN I Regional 7 has a utility factor of 2.198, indicating that the queueing system is overloaded. A utility rate greater than 1 signifies that the queueing system is not operating efficiently. This provides critical insights for PTPN I Regional 7 in designing more efficient HPS determination strategies based on the profile and needs of each work unit.